Distal Tibial Articular Fractures in Racing Greyhounds: A Review of Six Cases - Montavon, P. M.; Dee, J. F.; Weiss, R. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Six spontaneously occurring distal tibial fractures extending into the posterior articular margin of young racing greyhounds were reviewed. Concomitant fractures of both malleoli occurred in three cases. Fracture patterns, methods of treatment and functional results were determined. Open anatomical reduction and rigid internal fixation promoted healing with minimal osseous reaction and showed better results than conservative treatment. Complications adversely affecting the outcome were periarticular deformity and osteoarthritis, these were observed as early as five to seven weeks following the operations.Six spontaneously occurring distal tibial fractures extending into the posterior articular margin of young racing greyhounds were reviewed. Fracture patterns, methods of treatment and functional results were determined.
Keywords: Distal tibial articular fractures; open reduction and internal fixation; racing greyhounds